Sodium and Potassium Intake Assessed by Spot and 24-h Urine in the Population-Based Tromsø Study 2015–2016 - Haakon E. Meyer; Lars Johansson; Anne Elise Eggen; Heidi Johansen; Kristin Holvik (Nutrients, 2019)
Reduction of salt intake is a public health priority and necessitates the surveillance of salt intake in the population. The validity of salt intake assessed by dietary surveys is generally low. We, therefore, aimed to estimate salt intake by 24-h urine collection and to assess the usefulness of spot urine collection for surveillance purposes. In the population-based Tromsø Study 2015–2016, 493 men and women aged 40–69 years collected 24-h urine, of whom 475 also collected spot urine. Sodium and potassium excretions were calculated by multiplying respective urinary concentrations by the total volume of urine. Based on the sodium concentration in spot urine, we also estimated 24-h sodium excretion by three different equations. Mean sodium excretion was 4.09 ± 1.60 and 2.98 ± 1.09 g/24-h in men and women, respectively, corresponding to a calculated salt intake of 10.4 and 7.6 g. The sodium to potassium molar (Na/K) ratio was approximately 1.8 in both genders. Of the three equation utilizing spot urine, estimated mean 24-h sodium excretion was closest for the INTERSALT formulae (4.29 and 2.96 g/24-h in men and women, respectively). In this population-based study, the estimated salt intake was higher than the recommended intake. However, urine potassium excretion was rather high resulting in a favorable Na/K ratio. Mean sodium excretion calculated from spot urine by the INTERSALT equation predicted the mean sodium excretion in 24-h urine reasonably well.